2018
DOI: 10.1097/md.0000000000011885
|View full text |Cite
|
Sign up to set email alerts
|

The white substance may be a potential endoscopic marker for flat esophageal mucosal neoplastic lesions

Abstract: To determine whether the white substance can act as an endoscopic marker for flat esophageal mucosal neoplastic lesions.Esophageal mucosal neoplastic lesions are mainly identified using white light endoscopy, because it is cost-effective; however, this method is limited for detecting early esophageal cancer and precancerous lesions, because these are typically flat mucosal neoplastic lesions. In our experience, a white substance surrounds or covers some flat esophageal mucosal lesions that are eventually diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The results of this study showed that white substance was more common in females and patients aged 60-69 years (p < 0.05), but its incidence was not affected by lesion location and extent (low-grade, high-grade intraepithelial neoplasia, early squamous cell carcinoma) (p > 0.05). Previous studies showed that the distribution of white substance is not affected by sex or age (p > 0.05) [17] . This discrepancy may be because these previous studies were retrospective, and based on incomplete data on invasion depth, tumor metastasis, and other aspects.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The results of this study showed that white substance was more common in females and patients aged 60-69 years (p < 0.05), but its incidence was not affected by lesion location and extent (low-grade, high-grade intraepithelial neoplasia, early squamous cell carcinoma) (p > 0.05). Previous studies showed that the distribution of white substance is not affected by sex or age (p > 0.05) [17] . This discrepancy may be because these previous studies were retrospective, and based on incomplete data on invasion depth, tumor metastasis, and other aspects.…”
Section: Discussionmentioning
confidence: 82%
“…In a previous study, we found that white substance often appears in flat-type esophageal mucosal lesions, and has a high diagnostic specificity for flat esophageal mucosal neoplasia [17] . Early esophageal squamous cell carcinoma and precancerous lesions often appear in the form of flat esophageal mucosal lesions, which are, therefore, considered diagnostically relevant [18] .…”
Section: Introductionmentioning
confidence: 75%